2022
DOI: 10.1016/j.wombi.2021.09.008
|View full text |Cite
|
Sign up to set email alerts
|

No one asked us: Understanding the lived experiences of midwives providing care in the north west suburbs of Melbourne during the COVID-19 pandemic: An interpretive phenomenology

Abstract: Problem Within the Victorian healthcare system, a rapid response to the COVID-19 pandemic has necessitated frequent and ongoing changes to midwifery practice. Background Midwives are a vital workforce at risk of burnout, attrition, and trauma. Emotional consequences of the pandemic for midwives remain largely unknown. Aim To understand the lived experiences of midwives providing care in the north west suburbs of Melbourne, Victoria during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 32 publications
4
43
2
Order By: Relevance
“…In the Australian context, a number of qualitative studies have been performed to date from the perspective of midwives regarding provision of maternity care (20-22) and of women regarding their maternity care experiences (23,24). These largely align with the more general findings of this study, with midwives reporting challenges to provision of woman-centered care (20, 22), and difficulties coping with rapid changes to care (including telehealth) and "COVID-19 causing chaos" (20)(21)(22). As in this study, "silver linings" included the perceived positive impact of visiting restrictions on postnatal care (20,22).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the Australian context, a number of qualitative studies have been performed to date from the perspective of midwives regarding provision of maternity care (20-22) and of women regarding their maternity care experiences (23,24). These largely align with the more general findings of this study, with midwives reporting challenges to provision of woman-centered care (20, 22), and difficulties coping with rapid changes to care (including telehealth) and "COVID-19 causing chaos" (20)(21)(22). As in this study, "silver linings" included the perceived positive impact of visiting restrictions on postnatal care (20,22).…”
Section: Discussionsupporting
confidence: 66%
“…Regarding mental health and/or DFV specifically, our findings suggest that changes in maternity care delivery in Australia, with face-to-face visits later in pregnancy and fewer in number, are likely to compound the perinatal mental health and DFV impact of the pandemic, through delay in screening and care, and in some cases missed screening altogether. This issue was also noted by Hearn et al in their study of midwives in Melbourne, Australia, who repeatedly voiced concerns around screening for family violence and noting how unsafe this was to do by telephone ( 21 ). Our findings also suggest a disparity in screening and care impacts for women from diverse backgrounds, as the unit with the highest proportion of overseas-born and non-English speaking women had a significantly higher staff perception of negative impact of the pandemic on DFV and mental health screening and care.…”
Section: Discussionmentioning
confidence: 84%
“…Fear and anxiety from a new experience, as well as worry of unexpected results during care provision, infection, and death, as well as concern of maternal implications, social consequences of working in quarantine hospital, were all expressed by midwives in the current study. Previous studies have also shown these emotional manifestations [17][18][19] .…”
Section: Coworker Relationship Development Participants Expressed The...mentioning
confidence: 60%
“…Midwives in this study found difficulties when providing care because they did not feel qualified and lacked expertise. Previous studies have shown that these emotional manifestations exist 18 , 22 .…”
Section: Discussionmentioning
confidence: 94%
“…Stress impacts both midwives and the women they care for. The provision of woman-centered care is central to the practice of midwifery [ 12 ] and some of the restrictions and changes in practice arising from the COVID-19 pandemic have been reported to compromise this care, leading to professional stress and personal conflict [ 12 , 13 , 14 , 15 ]. Fear of contracting COVID-19 and the need to protect their own families have been noted to give rise to significant stress for many midwives [ 14 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%